2017
DOI: 10.1016/j.bpj.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

ICON: An Adaptation of Infinite HMMs for Time Traces with Drift

Abstract: Bayesian nonparametric methods have recently transformed emerging areas within data science. One such promising method, the infinite hidden Markov model (iHMM), generalizes the HMM that itself has become a workhorse in single molecule data analysis. The iHMM goes beyond the HMM by self-consistently learning all parameters learned by the HMM in addition to learning the number of states without recourse to any model selection steps. Despite its generality, simple features (such as drift), common to single molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 39 publications
(57 reference statements)
2
75
0
Order By: Relevance
“…In particular, analyzing data derived from mobile biomolecules within an illuminated confocal region breaks down the perennial parametric Bayesian paradigm that has been the workhorse of biophysical data analysis [16,44,55,60,70,92,96]. We argue here that BNPs-which provide principled extensions of Bayesian logic [31,93]-show promise in Biophysics [46,55,87,88,90,92] and give us a working solution to prior parametric challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, analyzing data derived from mobile biomolecules within an illuminated confocal region breaks down the perennial parametric Bayesian paradigm that has been the workhorse of biophysical data analysis [16,44,55,60,70,92,96]. We argue here that BNPs-which provide principled extensions of Bayesian logic [31,93]-show promise in Biophysics [46,55,87,88,90,92] and give us a working solution to prior parametric challenges.…”
Section: Discussionmentioning
confidence: 99%
“…While BNPs have had a deep impact on Data Sci-ence since their inception, they are relatively new to Biophysics with a handful of papers [18,47,73] published to date using BNPs in Biophysical applications [50,55,[87][88][89][90]92].…”
Section: Introductionmentioning
confidence: 99%
“…arrivals. The underlying theory, Bayesian nonparametrics (BNPs) [40], is a powerful set of tools still under active development and largely unknown to the physical sciences [4,39,[41][42][43][44][45][46][47][48].…”
Section: Fig 2 Estimates Of Diffusion Coefficients From Photon Arrivalmentioning
confidence: 99%
“…We found that cc-EM correctly predicts the number of states in 91% of cases, given a higher robustness to false positive detection than the MDL algorithm in (40), and with much less estimate errors as can be seen with the RMSE boxplots 5. We also compared our proposed cc-EM algorithm to a Bayesian non parametric approach using the xl-ICON framework (65) to assess their specificity wrt false positive event detection and their robustness to overfitting under mixed noises (AWGN+pink+shot). To do so, we simulated a single fake state with 100 randomly positioned impulses simulating fake events, and sequentially corrupted the resulting trace by both AWGN and pink noises, given a SNR of 1dB, which emphasizes the magnitude of the transitions by the time varying noise variance, and thus increasing the risk of detecting false positive short-lived states.…”
Section: F3 Robustness To the Sensor Baseline Driftmentioning
confidence: 99%